1999
DOI: 10.1021/la9808162
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Morphology of Microphase-Separated Structure and Phase Restructuring at the Surface of Poly[2-hydroxyethyl methacrylate-block-4-(7‘-octenyl)styrene] Diblock Copolymers Corresponding to Environmental Change

Abstract: Hydrophilic−hydrophobic diblock copolymers composed of 2-hydroxyethyl methacrylate (HEMA) and 4-(7‘-octenyl)styrene with 26, 47, and 82 wt % of poly[4-(7‘-octenyl)styrene], HO-30, -50, and -80, respectively, were synthesized by anionic living polymerization. The surface structures of their solvent-cast films under dry and wet conditions were analyzed by contact angle measurements, transmission electron microscopic (TEM) observation, and X-ray photoelectron spectroscopic (XPS) measurements. The analytical resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…[13] As the polymerization was not investigated in detail, some more polymerizations changing the ratios of [7] to [sec-BuLi] were carried out. In all cases, yields of polymers were quantitative.…”
Section: Anionic Polymerizations Of 7 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] As the polymerization was not investigated in detail, some more polymerizations changing the ratios of [7] to [sec-BuLi] were carried out. In all cases, yields of polymers were quantitative.…”
Section: Anionic Polymerizations Of 7 Andmentioning
confidence: 99%
“…Very recently, we [13] and Ruckenstein and Zhang [14,15] have independently reported the living anionic polymerizations of styrenes para-substituted with alkenyl groups, 8-(p-vinylphenyl)-1-octene and p-(3-butenyl)styrene whose alkenyl groups are not aryl-conjugated. The success of these living polymerizations can be supported by the fact that the addition reaction of carbanions to simple alkenes does not generally occur under normal conditions in contrast to the ready addition of carbanions to activated alkenes by aryl-conjugated such as the vinyl and isopropenyl groups of vinylbenzenes as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The Nakahama group [17,18] observed surface rearrangements of a hydrophilic-hydrophobic diblock co-polymer [poly(2-hydroxyethyl methacrylate-block-isoprene)] in response to aqueous environments using transmission electron microscopy and found that the hydrophobic surface enriched with polyisoprene segments under dry conditions was replaced with poly(2-hydroxyethyl 1742-7061/$ -see front matter Ó 2009 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [99] reported a switchable copolymer with poly(vinyl sugars) as hydrophilic pendant groups on PS, in which the contact angle could be decreased by 20-408 when surfaces were soaked in water. Senshu et al [100][101][102] also demonstrated polymer rearrangement and replacement of hydrophobic groups at the uppermost surface with hydrophilic groups when soaking diblock and triblock copolymer films in water. Again, drying could be used to restore the hydrophobic surface.…”
Section: Environmental Switchingmentioning
confidence: 99%